Oceanographic gradients explain changes in the biological traits of nesting seabird assemblages across the south-eastern Pacific - Gusmao, Joao B.; Luna-Jorquera, Guillermo; Rivadeneira, Marcelo M. (Frontiers in Marine Science, 2022)
Seabirds are top predators in coastal and pelagic ecosystems that forage at sea but return to land regularly during the breeding season (i.e., central place foragers). This unique life history strategy is directly related to their biological traits and helps define their role as top predators in marine systems. We analysed the effects of physiographic characteristics of nesting islands (area, elevation, and distance from the continent, as predicted by the General Dynamic Model of Oceanic Island Biogeography) and oceanographic variables from waters surrounding nesting islands that tend to be characterised by steep gradients (temperature, salinity, and primary productivity) on the trait diversity of nesting seabird assemblages on islands of the south-eastern Pacific Ocean. Four biological traits related to species’ life history and feeding strategy were used to calculate two indices, the Functional Richness and Rao’s Quadratic entropy. We used fourth-corner and RLQ analysis to determine the relationship between biological traits and environmental variables. Island physiography and primary productivity in the waters surrounding nesting islands significantly affected seabird trait diversity, which gradually decreased from Chilean coastal islands to the distant Polynesian Islands. The traits for body mass and clutch size showed a significant positive relationship with primary productivity. We identified three assemblages of seabirds that had contrasting trait structures. These were defined as the Galapagos, Coastal Chile, and south-eastern Oceanic islands assemblages, and reflected the adaptations of three different species pools to specific oceanographic conditions. Our results suggest that food-related constraints might be one of the most critical environmental filters that shaped the current trait structure of nesting seabird assemblages on the islands in the eastern South Pacific Ocean.